2020
DOI: 10.1002/gj.3810
|View full text |Cite
|
Sign up to set email alerts
|

Geochemistry and palynology of the upper Albian at the Abu Gharadig Basin, southern Tethys: Constraints on the oceanic anoxic event 1d

Abstract: The mid‐Cretaceous period was a time of abnormal polar temperature warming and consequent global oceanic anoxia that enhanced the widespread accumulation of organic matter‐rich marine sediments. The current contribution focuses on the late Albian oceanic anoxic subevent 1d (OAE 1d) that represents a period of increased perturbation of the global carbon cycle. Palynological and geochemical investigations, including TOC/Rock‐Eval pyrolysis and stable carbon isotope of organic matter (δ13CTOC), were conducted for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 75 publications
2
18
0
Order By: Relevance
“…Elemental geochemistry is the most extensively employed method for quantitatively reconstructing the paleoenvironment. , Generally speaking, organic carbon, phosphorus (P), and biogenic barium (Ba bio ) are the popular proxies for qualitatively evaluating the paleomarine productivity. Several redox-sensitive elements (e.g., V, U, and Ni) and their ratios (e.g., U/Th, V/Cr, Ni/Co, and V/(V + Ni)) have been widely applied to interpret the paleoredox conditions over the past couple of decades. ,,, REE distribution patterns and ratios of (La/Yb) N , Th/U, and Na/K are the important geochemical indices to qualitatively characterize the sedimentary rate. …”
Section: Introductionmentioning
confidence: 99%
“…Elemental geochemistry is the most extensively employed method for quantitatively reconstructing the paleoenvironment. , Generally speaking, organic carbon, phosphorus (P), and biogenic barium (Ba bio ) are the popular proxies for qualitatively evaluating the paleomarine productivity. Several redox-sensitive elements (e.g., V, U, and Ni) and their ratios (e.g., U/Th, V/Cr, Ni/Co, and V/(V + Ni)) have been widely applied to interpret the paleoredox conditions over the past couple of decades. ,,, REE distribution patterns and ratios of (La/Yb) N , Th/U, and Na/K are the important geochemical indices to qualitatively characterize the sedimentary rate. …”
Section: Introductionmentioning
confidence: 99%
“… 33 Based on palynofacies and palynomorph analyses, the Kharita Formation was deposited under successive oscillations between fluvio-deltaic to marginal and shallow marine environments. 11 The sedimentary record of the Kharita Formation is principally dominated by siliciclastic sediments that showed cyclic alternations between coarse-grained sandstones and siltstones and shales ( Figure 3 ). As a result, the T–R sequence stratigraphic model was used following the third-order approach to subdivide the Kharita Formation into distinctive stratigraphic units.…”
Section: Discussionmentioning
confidence: 99%
“…The Kharita Formation was investigated with a detailed focus on the late Albian oceanic anoxic event 1d by addressing biostratigraphy, assessing the depositional paleoenvironment, and evaluating the redox conditions and role of sediment fluxes based on palynofacies analysis and palynomorph composition as well as inorganic and isotope geochemistry. 11 Therefore, the present study aims to (1) employ the palynofacies and palynomorph composition along with the geophysical gamma ray log data and the lithological characteristics of the Kharita Formation to reconstruct the relative sea-level fluctuations and subdivide them into distinctive systems tracts and stratigraphic sequences and (2) compare the sequence stratigraphic reconstructions based on the major and trace elemental geochemical composition to the results obtained from the palynofacies and palynomorph composition.…”
Section: Introductionmentioning
confidence: 99%
“…Paleoproductivity refers to the total amount of organic matter fixed per unit area per unit time (Algeo et al, 2011;Pan et al, 2020). Generally speaking, high organic productivity is one of the key factors for the formation of hydrocarbon source rocks (Talbot, 1988;Nelson et al, 1995;Mansour et al, 2020a;Mansour et al, 2020b;Yang et al, 2016;Zhao et al, 2021), and a large number of studies have shown that siliceous plankton in marine source rocks is the main provider of marine primary productivity (De Wever and Baudin, 1996;Chou et al, 2012;Xiang et al, 2013;Shaldybin et al, 2017;Jiang et al, 2019;Zhang et al, 2019), whose content is closely related to the biological reproduction in surface water, and its temporal and spatial distribution can be used to reflect the changing process of paleoproductivity. In recent years, many studies have shown that radiolarians enriched in marine hydrocarbon source rocks can gather together and absorb a lot of symbiotic algae in their bodies by using a large number of pseudopodia, forming a good symbiotic relationship with them (Lyle et al, 1988;Erbacher and Thurow, 1997;Xiang et al, 2013;Khan et al, 2019).…”
Section: Relationship Between Biogenic Silica and Organic Mattermentioning
confidence: 99%